Influence of mining-induced ground fissures on soil infiltration characteristics and its erosion effect in coal mining area of northern Shaanxi in the middle reaches of the Yellow River - Shijie SONG; Xing CHENG; Shuangming WANG; Lu LIU; Yuanhong LI; Jiajie ZHANG; Baodeng CHEN (Meitan xuebao)
Cracking the soil and water loss effects of mining-induced surface fissures in the coal mining area of the middle reaches of the Yellow River is of great significance for ecological environment protection and high-quality development in the coal mining region of northern Shaanxi. Taking the soil around the mining-induced ground fissures with widths of 0−10, 10−20, 20−30 cm (within 80 cm in horizontal distance and shallower than 20 cm in vertical depth) in the typical mining-induced ground fissure development area in the north wing of Ningtiaota mine field in northern Shaanxi as the research object, the soil infiltration rate, cumulative infiltration, saturated hydraulic conductivity (Ks), organic matter, mechanical composition and > 0.25 mm water-stable aggregates were measured by constant head method and instrument analysis method, respectively. The influence of mining-induced ground fissures on soil infiltration characteristics was revealed. Based on the RUSLE2 model calculation, the soil erosion effect on the small spatial scale of mining-induced ground fissures considering infiltration characteristics is clarified. The results showed that: ① The infiltration rate of soil around the mining-induced fissures exhibits a dynamic variation process over time, characterized by three stages: transient (0−3 min), gradual (3−60 min), and stable (60−110 min). ② The effect of mining-induced ground fissure development on soil Ks is the most significant, with an average increase of 60.63%. This effect increases with the increase of mining-induced ground fissure width and the decrease of horizontal distance from ground fissure. ③ Soil cumulative infiltration and Ks were significantly positively correlated with very fine sand (p < 0.01), but significantly negatively correlated with clay and organic matter (p < 0.01), and significantly negatively correlated with > 0.25 mm water-stable aggregates (p < 0.05). ④ The variation range of erodibility K-value calculated by considering infiltration characteristics is 1.12−2.13 times larger than that without considering infiltration characteristics. Based on the exponential function, the prediction model of the influence range of mining-induced ground fissures with different widths on the infiltration rate and erodibility K-value of the surrounding soil was constructed. It was found that when the horizontal distance from the mining-induced ground fissures exceeded 226 cm and 157 cm, respectively, the effect of mining-induced ground fissures on increasing the infiltration rate and erodibility of the surrounding soil basically disappeared. It can be used as a precise prevention and control target area for soil erosion in the loess mining-induced ground fissure development area in the middle reaches of the Yellow River.